Optimization and Rule Analysis of Drawdown Level before Flood Season of Longtan Hydropower Station - LIU Yongqi; HOU Guibing; GAO Weishan; LI Yuanyuan; WANG Baohua; LI Peng (Renmin Zhujiang)
Longtan Hydropower Station is the controlled reservoir of the Hongshui River.It is of significance for flood control,water supply,and power safety to study the optimal drawdown level before flood seasons in this station.Based on analyzing the drawdown level and operation requirements of Longtan Hydropower Station,this paper develops an operation model for the optimal drawdown of the station and solves the model efficiently by the evolutionary algorithm.Then,the optimization rule of the drawdown level in Longtan Hydropower Station is analyzed in depth and derived based on the multi-year optimal operation scheme set.The results show that the multi-year average power generation efficiency of cascade reservoirs can be significantly improved by optimizing the drawdown level process before flood seasons in Longtan Hydropower Station.Additionally,the derived operation rule can provide technical support for actual operations.